A study on various risk factors involved in benign gastrointestinal perforations in rural population of tri-state border - Venkatesan, Arjun Karthik Muthukrishnan; Amudala, Abhiram; Chidamber Rao, Channanna; Dasari , Kavya (International Surgery Journal, 2024)
Background: Gastrointestinal perforation is a common surgical emergency encountered by surgeons worldwide. Benign gastrointestinal perforations are especially prevalent in rural populations, leading to significant mortality and often requiring emergency surgery. This study was aimed to investigate the association of various risk factors of benign gastrointestinal perforations in the Tristate border of Tamil Nadu, Andhra Pradesh and Karnataka, thereby assessing the prognosis and surgical outcome. Methods: A prospective observational study was conducted from March 2023 to March 2024 at the Department of General Surgery, PESIMSR, KUPPAM. The study included a total of 50 patients with perforation features, selected using purposive sampling technique. A detailed medical history was taken, physical examination and relevant investigations were conducted, and the findings were correlated with intraoperative and histopathology reports. The patients were followed up for complications. The data was analysed with appropriate statistical methods. Results: Out of 50 patients, 72% were males and 28% were females. The most common age range of presentation was 41-50 years. The leading cause of perforation was peptic ulcer, accounting for 46% of cases, followed by appendicitis in 22% of cases, typhoid in 18% of cases, trauma in 12% of cases, and tuberculosis in 2% of cases. Mortality was observed in 7 cases (14%). It’s important to note that multiple organ dysfunction syndrome (MODS) and mortality were linked to a higher Mannheim peritonitis prognostic index, indicating a poor prognosis. Conclusion: Early diagnosis with risk factors assessment, immediate fluid resuscitation, and timely surgical intervention are crucial in significantly lowering the mortality rate associated with perforated peritonitis.